Sleep Spindles and Fragmented Sleep as Prodromal Markers in a Preclinical Model of LRRK2-G2019S Parkinson's Disease - Crown, Lindsey M.; Bartlett, Mitchell J.; Wiegand, Jean-Paul L.; Eby, Allison J.; Monroe, Emily J.; Gies, Kathleen; Wohlford, Luke; Fell, Matthew J.; Falk, Torsten; Cowen, Stephen L. (Frontiers in Neurology, 2020)
Sleep disturbances co-occur with and precede the onset of motor symptoms in Parkinson’s disease (PD). We evaluated sleep fragmentation and thalamocortical sleep spindles in mice expressing the p.G2019S mutation of the leucine-rich repeat kinase 2 (LRRK2) gene, one of the most common genetic forms of PD. Thalamocortical sleep spindles are oscillatory events that occur during slow-wave sleep that are involved in memory consolidation. We acquired data from electrocorticography, sleep behavioral measures, and a rotarod-based motor enrichment task in 28 LRRK2-G2019S knock-in mice and 27 wild-type controls (8-10 month-old males). Sleep was more fragmented in LRRK2-G2019S mice; sleep bouts were shorter and more numerous, even though total sleep time was similar to controls. LRRK2-G2019S animals expressed more sleep spindles, and individual spindles were longer in duration than in controls. We then chronically administered the LRRK2-inhibitor MLi-2 in-diet to n=12 LRRK2-G2019S and n=15 wild-type mice for a within-subject analysis of the effects of kinase inhibition on sleep behavior and physiology. Treatment with MLi-2 did not impact these measures. The data indicate that the LRRK2-G2019S mutation could lead to reduced sleep quality and altered sleep spindle physiology. This suggests that sleep spindles in LRRK2-G2019S animals could serve as biomarkers for underlying alterations in sleep networks resulting from the LRRK2-G2019S mutation, and further evaluation in human LRRK2-G2019S carriers is therefore warranted.